IKTERUS NEONATORUM - Maulida, Luluk Fajria (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT The word jaundice is derived from the French word "jaune which means yellow. Jaundice is a yellow discoloration of the skin, mucous membranes, and sclera due to increased production of bilirubin in the blood. This situation indicates an increased bilirubin production or elimination of bilirubin from the bodys ineffective. Neonatal jaundice is divided into two physiologic jaundice and pathologic jaundice. Causes of neonatal jaundice is excessive bilirubin production, disruption in the "uptake" and conjugation result of impaired liver function, impaired transport process due to the lack of albumin increased indirect bilirubin and excretion disorder caused by blockage of the liver due to infection or damage to liver cells (congenital abnormalities). One way to do for checking the degree of yellow in the neonatal by Kramer is with the forefinger emphasized in places like bone protruding bones, nose, chest, knees. Complications heaviest newborn jaundice is bilirubin encephalopathy or jaundice kern. Management of jaundice there are several kinds of light therapy (phototherapy / blue light), exchange transfusion, optimal breastfeeding and sunlight therapy. Â  Keywords: jaundice, neonatal, management